Review Pengaruh Penambahan Nanopartikel Pada Pelumas Terhadap Oli Mesin - Dimas Maha Saputra; Dan Mugisidi (Prosiding Seminar Nasional Teknoka, 2025)
Improving engine efficiency and stability is a key component of engine technology, especially in the crucial aspect of lubrication to reduce friction and component wear. Conventional lubricants often have difficulty in maintaining thermal stability and tribological properties under high operating conditions. Therefore, the use of nanoparticles in lubricants is being developed as an innovation to improve engine performance. This review aims to analyze the effect of various types and concentrations of nanoparticles on the physical characteristics and performance of lubricants, such as viscosity, thermal conductivity, and the ability to reduce friction. The method used is an experiment in which metal oxide nanoparticles are mixed into the base oil using an ultrasonic method, followed by using a viscometer and tribometer. The findings of this review show that the addition of nanoparticles can significantly improve thermal stability and reduce the coefficient of variation of friction compared to oil without nanoparticle additives. This indicates that nanoparticle-based lubricants have the potential to improve engine and component efficiency.